2016
DOI: 10.1530/joe-16-0040
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila ortholog of TMEM18 regulates insulin and glucagon-like signaling

Abstract: Transmembrane protein 18 (TMEM18) is an ill-described, obesity-related gene, but few studies have explored its molecular function. We found single-nucleotide polymorphism data, suggesting that TMEM18 may be involved in the regulation/physiology of metabolic syndrome based on associations with insulin, homeostatic model assessment-β (HOMAβ), triglycerides, and blood sugar. We then found an ortholog in the Drosophila genome, knocked down Drosophila Tmem18 specifically in insulin-producing cells, and tested for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Therefore, we speculated that the locus near TMEM18 (rs6548238) may increase diabetes risk via inducing obesity and insulin resistance. An experimental study in Drosophila found that TMEM18 affected substrate levels via insulin and glucagon signaling [24]. Further functional studies are needed to understand the mechanisms by which the locus near TMEM18 (rs6548238) regulates the development of obesity and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculated that the locus near TMEM18 (rs6548238) may increase diabetes risk via inducing obesity and insulin resistance. An experimental study in Drosophila found that TMEM18 affected substrate levels via insulin and glucagon signaling [24]. Further functional studies are needed to understand the mechanisms by which the locus near TMEM18 (rs6548238) regulates the development of obesity and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although variants related to this gene have been associated with BMI and insulin concentrations, little is known of its function. A study in Drosophila melanogaster implicated TMEM18 in insulin/glucagon regulation [ 64 ]. The variant rs11676272 is among the SNPs most strongly associated with childhood adiposity and is also nominally associated with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is the transmembrane protein 18 ( TMEM18 ) gene. TMEM18 is expressed throughout the body and plays a role in the regulation of body weight, appetite, and even in the development of obesity [48,49]. Another gene on chromosome 18 is the melanocortin-4 receptor ( MC4R ), whose risk allele is associated with 0.23 kg/m 2 higher BMI [42].…”
Section: Genetics and Obesitymentioning
confidence: 99%